2017
DOI: 10.1016/j.jdiacomp.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

High rates of severe hypoglycemia among African American patients with diabetes: the surveillance, prevention, and Management of Diabetes Mellitus (SUPREME-DM) network

Abstract: Aims Seven-year surveillance study (2005–2011) to evaluate race/ethnic differences in the trends in rates of severe hypoglycemia (SH) in a population of insured, at-risk adults with diabetes. Methods SH events were identified via any primary or principal diagnosis from emergency department or inpatient encounters among African American, Asian, Latino and White adult diabetes patients treated with insulin or secretagogues (Sulfonylureas or Meglitinides), receiving care from integrated healthcare delivery syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
4
26
2
Order By: Relevance
“…Our finding that blacks are at higher risk of hypoglycemia is consistent with those of prior studies (6,810,27) demonstrating major racial disparities in hypoglycemia risk. In sensitivity analyses, we found that the observed racial disparities were not entirely explained by the available metrics of socioeconomic status.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding that blacks are at higher risk of hypoglycemia is consistent with those of prior studies (6,810,27) demonstrating major racial disparities in hypoglycemia risk. In sensitivity analyses, we found that the observed racial disparities were not entirely explained by the available metrics of socioeconomic status.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence rates of severe hypoglycemia in our study (range in demographic groups 6–25/1,000 person-years) are similar to other studies of persons with type 2 diabetes and attest to the high burden of hypoglycemia in the community (4,10,14,24). Our results extend the evidence for risk factors previously identified in the literature.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Observational analyses conducted in North America reported higher rates of severe hypoglycaemia and hospital admission for hypoglycaemia in African-Americans, compared with other ethnicities [14,[21][22][23][24]. Moreover, a recent study in England has confirmed a different risk of hypoglycaemia in people with diabetes of diverse ethnicity, reporting a 60% higher risk of hospital admission for severe hypoglycaemia in people of Caribbean descent, compared with those of European descent, accounting for socioeconomic differences [25].…”
Section: Discussionmentioning
confidence: 99%